EDUCATION ON DISASTER PREPAREDNESS AND RESPONSE OF DENTAL HYGIENISTS IN VOCATIONAL UNIVERSITIES/COLLEGES IN JAPAN - Takafuji, Mari; Kishida, Aoi; Takamatsu, Kunihiko; Nakata, Yasuo; Adachi, Ryohei (PEOPLE: International Journal of Social Sciences, 2018)
Due to the increasing global frequency of disasters, disaster preparedness training is becoming more important. The fact that Japan has many earthquakes is well known worldwide. In the field of nursing, the importance of disaster preparedness education in universities has gradually increased in Japan. Many people lose their homes in earthquakes and have to live in shelters. The relationship between pneumonia and the oral cavity environment is understood; for example, in certain shelter environments that provide an insufficient water supply, oral cavity hygiene is affected. Keeping a clean oral cavity prevents death from pneumonia, especially in elderly people. To keep a clean oral cavity, the role of dental hygienists is important. In Japan, education on disaster preparedness and response for dental hygienists in vocational university/college is rarely provided. Therefore, this is the focus of our research. We administered an anonymous questionnaire survey to 119 dental hygienist training schools by mailing them surveys asking about their education on disaster preparedness and response for dental hygienists. In this paper, we report on the education on disaster preparedness and response for dental hygienists in vocational universities and colleges in Japan.